vp100813_elic_PronominalForms_kto - Валентина Пуяковна Силкина (Надер); Олеся Ханина (Bernard Comrie, 2010)
O.Khanina collects with V.P.Nader the paradigm of the pronoun SiO 'who' тундровый энецкий, русский Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100813_elic_PronominalForms_kto